The utilization of drone emprit in seeing the trend of increasing oil fuel through social media data - Wahyuddin S; Zul Rachmat; Abdillah Abdillah; Andi Irfan; Muhammad Idris (Institute of Computer Science (IOCS), 2023)
This study investigates the use of drone emprit as a tool to monitor the trend of increasing fuel prices through analysis of data obtained from social media platforms using twitter. The aim of this study is to develop a new approach in understanding and forecasting fuel price fluctuations by utilizing widely available data on social media. The research combines drone emprit technology to get a visual picture of the situation at various fuel distribution sites, and integrates it with text and sentiment analysis taken from social media platforms. The methodology used includes visual data collection using drone emprit, collection of text data from social media platforms, and integrated data processing and analysis. The results of this study are expected to provide deeper insights into the factors influencing fuel price increases, including social and economic factors reflected in online conversations. By combining visual data and text analysis, the study contributes to the development of new methodologies for understanding and forecasting economic trends using innovative data sources.